Pelatihan “Goal Setting” untuk Meningkatkan Orientasi Masa Depan pada Siswa SMP - Farhan Zakariyya; koentjoro koentjoro (Faculty of Psychology, Universitas Gadjah Mada, 2017)
Future orientation of junior high school students is an orientation in the educational field. Students are faced with choices of the next level of their study, which is either to senior high school, Islamic senior high school (MA), or vocational high school with choices of interests/specializations. Students are expected to choose the continuation of their study according to their abilites, interest, and aptitude. However, the students find it hard to determine their future orientation. This present study aims at examining whether “Goal setting” training can improve the future orientation of junior high school students. The subjects in this study are 45 students aged 13-14 years (21 students into the experimental group and 24 students to a control group) junior high school students who earn a medium score in the scale of future orientation and goal setting. The experimental design employed in this study is untreated group control design with dependent pretest and posttest samples. The data analysis that is used is Independent Samples t-test. The results showed that the